Effects of the Project-Based Learning Model on Students’ Learning Outcomes: A Meta Analysis - Intan Purnama Yani; Asrizal Asrizal; Usmeldi Usmeldi (Jurnal Penelitian Pembelajaran Fisika, 2025)
Twenty first century education faces a major challenge to prepare students with relevant skills in facing the rapid advancement of technology. One approach that is widely recognized as being able to answer this challenge is the project-based learning model or Project-Based Learning (PjBL). This model emphasizes contextual learning, where students are actively involved in designing, developing, and completing projects that are relevant to the real world. With this approach, students not only learn cognitively but also develop critical thinking skills, collaboration, communication, and creativity. However, although many studies show the advantages of PjBL, the results reported are often diverse and sometimes contradictory. Several studies show that PjBL significantly improves student learning outcomes, both in cognitive, affective, and psychomotor aspects. In contrast, other studies report less significant or even inconsistent impacts. This raises questions about how much influence PjBL has overall on learning outcomes, and what factors influence the effectiveness of this model. To answer this question, a synthesis of data from various studies is needed through a meta-analysis approach. This approach allows researchers to integrate quantitative data from various studies and produce more comprehensive conclusions. This study aims to evaluate the influence of the PjBL model on student learning outcomes as a whole, as well as to identify moderator variables that influence the success of its implementation. The results of the study are expected to provide significant contributions to the development of educational policies and teaching practices at various levels of education.